Kepribadian Tokoh dalam Kumpulan Naskah Drama Perjuangan Laskar Tujuh Belas Karya Ari Sulistyo - Nuraini Nuraini; Noni Andriyani (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research is motivated by several things, namely (1) Seeing the many aspects of literary psychology in the collection of drama scripts of the struggle of the Seventeen Laskar by Ari Sulistyo. (2) Research on drama scripts using literary psychology theory is rarely done, because most people are more familiar with a drama through performances than reading the drama script itself. Personality psychology is the study of human personality with the object of research on factors that influence human behavior. In personality psychology studied the relationship between memory or observation with development, the relationship between observation and adjustment to the individual. According to Freud, "the intricacies of the human psyche are composed of three levels, namely: the id (basic drive), ego (conscious regulation between the id and external reality), and the superego (the moral guide of one's aspirations). The method in this study is a descriptive method, namely describing and presenting data according to the content analysis or the actual situation about the personality of the character in the drama Laskar Tujuh Belas by Ari Sulistyo. The data collection technique in this study is a hermeneutic technique, namely reading, note-taking, and inference techniques. The data obtained in this study were analyzed with the following steps: (1) classifying the data obtained based on the problems of the id, ego, and superego, (2) analyzing the data that has been grouped based on Sigmund Freud's personality theory, (3) concluding data belonging to the personality of the character according to Sigmund Freud's theory, and (4) the data is presented in the analysis and interpretation of the data. The results of the study explain that literary psychology related to the personality of the id element is more dominant than the ego and superego elements. From the data that has been grouped as many as 34 data, 17 data of which are the id element which is psychic energy and instincts that press humans to fulfill basic needs, 11 data on the ego element which is the only area of ​​the mind that has contact with reality, and 6 superego element data.